2011
DOI: 10.1111/j.1365-2966.2011.19116.x
|View full text |Cite
|
Sign up to set email alerts
|

An unbiased sample of bright southern compact steep spectrum and gigahertz peaked spectrum sources

Abstract: Compact Steep Spectrum (CSS) and Gigahertz Peaked Spectrum (GPS) sources are classes of compact, powerful, extragalactic objects. These sources are thought to be the earliest stages in the evolution of radio galaxies, capturing the ignition (or, in some cases, re‐ignition) of the active galactic nucleus. As well as serving as probes of the early stages of large‐scale radio sources, these sources are good, stable, amplitude calibrators for radio telescopes. We present an unbiased flux density limited (>1.5 Jy a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 71 publications
5
41
0
Order By: Relevance
“…It is an archetypal GPS radio source (Randall et al 2011), peaking at an observed frequency of 1 GHz, with optically thick and thin spectral indices 4 of α = 0.83 and −0.74, respectively (see Fig. 1).…”
Section: Pks B1740−517mentioning
confidence: 99%
“…It is an archetypal GPS radio source (Randall et al 2011), peaking at an observed frequency of 1 GHz, with optically thick and thin spectral indices 4 of α = 0.83 and −0.74, respectively (see Fig. 1).…”
Section: Pks B1740−517mentioning
confidence: 99%
“…The compact inverted-spectrum AGN core is similar to gigahertz-peaked spectrum sources (GPSs) that exhibit a peak in their radio spectra between 1 and 5 GHz and an inverted-shape spectrum at lower frequencies (Fanti 2009). GPSs are interpreted as radio AGNs in early phases of their evolution; therefore, compact inverted-spectrum radio cores of TDRGs may be considered as an indication of recent AGN activity (Randall et al 2011;Orienti 2016). Indeed, some DDRGs are known to show a mildly inverted spectrum of the core (Machalski et al 2010).…”
Section: Radio Morphologymentioning
confidence: 99%
“…CSS and gigahertz-peaked spectrum (GPS) galaxies are bright radio sources, which are considered to be young radio galaxies based on their peaked radio spectra and compact jet structure (e.g., O'Dea 1998;Stanghellini 2003;Fanti et al 2011;Randall et al 2011, and references therein). The same scenario has been discussed for γ-NLS1 due to their low black hole masses and high accretion rates (e.g., Foschini et al 2015).…”
Section: Comparison With Compact Steep-spectrum Sourcesmentioning
confidence: 99%